Cyberwar as a Phenomenon of Asymmetric Threat and Cyber-Nuclear Security Threats - Аліка Гучуа; Торніке Зеделашвілі (Історико-політичні проблеми сучасного світу, 2019)
The work deals with the topic of cyberwar as a phenomenon of asymmetric threat and cyber-nuclear security threats in modern world politics, potential threats to international politics and global security issues, counter-terrorism policies are discussed. The paper discusses the challenges facing cyber security worldwide and the phenomenon of cyber security against the backdrop of asymmetric threats. Cyberspace has already become a weapon of infinite capacity for the whole world. It has generated positive effect as well as has become the area of evil for terrorists, which are actively using modern technologies, computer systems. The facts are many and we are often in the center of events. With the development of technology in the 21st century, global changes are taking place in international security, the geopolitical transition and new threats and challenges, and international security issues are becoming increasingly important. The international security system is vulnerable to challenges such as the use of weapons of mass destruction and cyber terrorism. The article discusses the dangers and problems of hybrid warfare in international security, as well as the Russian-Georgian hybrid warfare.